
24×(11/12-3/8-1/6÷1/3) (2/3-0.4)÷(1/6+0.5) 3/4-1/9+8/15÷16/25 简算 帮我
展开全部
24×(11/12-3/8-1/6÷1/3)
=24*(11/12-3/8-1/2)
=22-9-12
=1
(2/3-0.4)÷(1/6+0.5)
=(2/3-4/10)/(2/3)
=1-4/10*3/2
=1-2/5
=3/5
3/4-1/9+8/15÷16/25
=3/4-1/9+8/15*25/16
=3/4-1/9+5/6
=9/12+10/12-1/9
=19/12-1/9
=(57-4)/36
=53/36
=24*(11/12-3/8-1/2)
=22-9-12
=1
(2/3-0.4)÷(1/6+0.5)
=(2/3-4/10)/(2/3)
=1-4/10*3/2
=1-2/5
=3/5
3/4-1/9+8/15÷16/25
=3/4-1/9+8/15*25/16
=3/4-1/9+5/6
=9/12+10/12-1/9
=19/12-1/9
=(57-4)/36
=53/36
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询